2016
DOI: 10.3889/oamjms.2016.063
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Cholesterol in COPD Patients with Severe and Very Severe Stage of the Disease

Abstract: BACKGROUND:High blood cholesterol is part of metabolic syndrome and can be caused by medical conditions or bad dietary habits.AIM:The aim of the study was to investigate the prevalence of hypercholesterolemia in privies diagnosed patients with the severe and very severe stage of COPD, which were stable.MATERIAL AND METHODS:We investigated 100 subjects, all of them smokers, with smoking status >10 years, stratified into two groups: with severe and very severe stage of the disease. It was clinical, randomized, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 22 publications
1
23
2
1
Order By: Relevance
“…Ivanovska 28 reported that total cholesterol and LDLcholesterol levels of severe COPD patients were significantly higher, which is different from the results of this study. Fasting blood glucose and HbA1c was greater in the COPD group than the NCOPD group, and both groups were pre-diabetic.…”
contrasting
confidence: 99%
“…Ivanovska 28 reported that total cholesterol and LDLcholesterol levels of severe COPD patients were significantly higher, which is different from the results of this study. Fasting blood glucose and HbA1c was greater in the COPD group than the NCOPD group, and both groups were pre-diabetic.…”
contrasting
confidence: 99%
“…Consequently, the level of cholesterol was high in the severe stage COPD patients, which may due to their life style modifications, such as restricted diet, poor lung function and ex-smoker status. 4,16 In present study, high triglycerides, low HDL cholesterol, and high LDL cholesterol, and low TCH were observed, especially in severe stage in comparison to moderate stage of COPD patients; however, these values were statistically significant in HDL and LDL parameters among COPD, moderate and severe stages.…”
Section: Discussioncontrasting
confidence: 54%
“…The occurrence of COPD in India is 4.1%. 3,4,5 In patients with COPD, smoking is considered as main risk factor. Various studies have concluded disarrangement of lipoprotein parameters as effects of tobacco smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 8 of the ratios of glycerophospholipids to cholesterol ester were lower in COPD groups, while the rest 2 lipid ratios biomarkers were higher in COPD groups. Patients with severe COPD have a higher level of cholesterol in the blood [ 33 ]. The upregulation of cholesterol could be partially due to the adverse effects of cigarette smoking on lipoprotein regulation [ 34 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous data [ 66 ], the major format of cholesterol ester is C18:2 CE as shown in Supplemental Table 1 . Patients with very severe COPD have a much higher level of cholesterol [ 33 , 35 ]. Interestingly, our results indicated the ratio of C16:1 CE in patients with COPD is about 3 times higher than that in healthy controls.…”
Section: Discussionmentioning
confidence: 99%